2022
DOI: 10.3390/ma15020567
|View full text |Cite
|
Sign up to set email alerts
|

On the Corrosion Fatigue of Magnesium Alloys Aimed at Biomedical Applications: New Insights from the Influence of Testing Frequency and Surface Modification of the Alloy ZK60

Abstract: Magnesium alloys are contemporary candidates for many structural applications of which medical applications, such as bioresorbable implants, are of significant interest to the community and a challenge to materials scientists. The generally poor resistance of magnesium alloys to environmentally assisted fracture, resulting, in particular, in faster-than-desired bio-corrosion degradation in body fluids, strongly impedes their broad uptake in clinical practice. Since temporary structures implanted to support ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 115 publications
0
6
0
Order By: Relevance
“…An extremely important aspect of implant materials testing is the loading frequency, which, in the case of corrosion fatigue, must be regulated in a much narrower range than in conventional tests in air. For example, an increase in the frequency from 10 Hz to 80 Hz for the popular extruded alloy ZK60 leads to an increase in the endurance limit by more than 1.4 times in Ringer’s solution on the basis of 5 × 10 5 loading cycles [ 231 ].…”
Section: Environmentally Affected Mechanical Responsementioning
confidence: 99%
See 2 more Smart Citations
“…An extremely important aspect of implant materials testing is the loading frequency, which, in the case of corrosion fatigue, must be regulated in a much narrower range than in conventional tests in air. For example, an increase in the frequency from 10 Hz to 80 Hz for the popular extruded alloy ZK60 leads to an increase in the endurance limit by more than 1.4 times in Ringer’s solution on the basis of 5 × 10 5 loading cycles [ 231 ].…”
Section: Environmentally Affected Mechanical Responsementioning
confidence: 99%
“…Fatigue tests were carried out on an Instron ElectroPuls E1000 machine with an alternating loading cycle on corset-type specimens with a nominal cross-section of 2 × 2 mm 2 . The testing conditions were the same as those described in [ 231 ].…”
Section: Environmentally Affected Mechanical Responsementioning
confidence: 99%
See 1 more Smart Citation
“…The ZK60 alloy was chosen as a typical representative of a class of wrought Mg alloys suffering from high susceptibility to PESCC. The grain microstructure and distribution of primary and secondary phases in the commercial hot-extruded alloy used in this work were documented in detail in the previous reports [ 24 , 25 , 30 , 31 ] by the present and other investigators; interested readers are encouraged to review the above-cited publications.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Localized galvanic corrosion should be avoided when considering developing alloys for bioresorbable applications as it can result in premature failure of the device. [24,25] Following thermal processing of MgRE alloys, a more random texture can be recrystallized, termed the "RE texture," which improves ductility and reduces the anisotropy of these alloys. [26] The origin of the RE texture is not fully understood; however, it has been shown that its appearance post thermal treatment can depend upon the previous processing steps, composition of RE elements in the alloy, and the annealing temperature.…”
Section: Introductionmentioning
confidence: 99%